PERFORMANCE CHARACTERISTICS OF A FRET-BASED IMMUNOASSAY FOR QUANTITATION OF INFLIXIMAB ON A POINT-OF-CARE INSTRUMENT SYSTEM. (21st January 2021) - Ong, Edgar; Huang, Ruo; Kirkland, Richard; Hale, Michael; Mimms, Larry
Abstract: Introduction: A fast (<5 min), time-resolved fluorescence resonance energy transfer (FRET)-based immunoassay was developed for the quantitative detection of infliximab (IFX) and biosimilars for use in therapeutic drug monitoring using only 20 µL of fingerstick whole blood or serum at the point-of-care. The Procise IFX assay and ProciseDx analyzer are CE-marked. Studies were performed to characterize analytical performance of the Procise IFX assay on the ProciseDx analyzer. Methods: Analytical testing was performed by spiking known amounts of IFX into negative serum and whole blood specimens. Analytical sensitivity was determined using limiting concentrations of IFX. Linearity was determined by testing IFX across the assay range. Hook effect was assessed at IFX concentrations beyond levels expected to be found within a patient. Testing of assay precision, cross-reactivity and potential interfering substances, and biosimilars was performed. The Procise IFX assay was also compared head-to-head with another CE-marked assay: LISA-TRACKER infliximab ELISA test (Theradiag, France). The accuracy of the Procise IFX assay is established through calibrators and controls traceable to the WHO 1 st International Standard for Infliximab (NIBSC code: 16/170). Results: The Procise IFX assay shows a Limit of Blank, Limit of Detection, and Lower Limit of Quantitation (LLoQ) of 0.1, 0.2, and 1.1 µg/mL in serum and 0.6, 1.1, and 1.7 µg/mL in whole blood, respectively. The linear assay range was determined to be 1.7 to 77.2 µg/mL in serum and whole blood. No hook effect was observed at an IFX concentration of 200 µg/mL as the value reported as ">ULoQ". Assay precision testing across 20 days with multiple runs and reagent lots showed an intra-assay coefficient of variation (CV) of 2.7%, an inter-assay CV of <2%, and a total CV of 3.4%. The presence of potentially interfering/cross-reacting substances showed minimal impact on assay specificity with %bias within ±8% of control. Testing of biosimilars (infliximab-dyyb and infliximab-abda) showed good recovery. A good correlation to the Theradiag infliximab ELISA was obtained for both serum (slope=1.01; r=0.99) and whole blood (slope=1.01; r=0.98) samples (Figure 1). Conclusion: Results indicate that the Procise IFX assay is sensitive, specific, and precise yielding results within 5 minutes from both whole blood and serum without the operator needing to specify sample type. Additionally, it shows very good correlation to a comparator assay that takes several hours and sample manipulation to yield results. This makes the Procise IFX assay ideal for obtaining fast and accurate IFX quantitation, thus allowing for immediate drug level dosing decisions to be made by the physician during patient treatment.